Adaptive Regulation of Nitrate Transceptor NRT1.1 in Fluctuating Soil Nitrate Conditions - Rashid, Mubasher (iScience, 2018)
Plant adaptation in variable soil nitrate concentrations involves sophisticated signaling and transport systems that modulate a variety of physiological and developmental responses. However, we know very little about their molecular mechanisms. It has recently been reported that many of these responses are regulated by a transceptor NRT1.1, a transporter cum receptor of nitrate signaling. NRT1.1 displays dual-affinity modes of nitrate binding and establishes phosphorylated/non-phosphorylated states at the amino acid residue threonine 101 in response to fluctuating nitrate concentrations. Here we report that intrinsic structural asymmetries between the protomers of the homodimer NRT1.1 provide a functional basis for having dual-affinity modes of nitrate binding and play a pivotal role for the phosphorylation switch. Nitrate-triggered local conformational changes facilitate allosteric communications between the nitrate binding and the phosphorylation site in one protomer, but such communications are impeded in the other. Structural analysis therefore suggests the functional relevance of NRT1.1 interprotomer asymmetries.